E-057 Direct vs indirect revascularization for moyamoya: a large multicenter study. (23rd July 2022) - El Naamani, K; Chen, C; Jabre, R; Saad, H; Grossberg, J; Dmytriw, A; Patel, A; Khorasanizadeh, M; Ogilvy, C; Thomas, A; Monteiro, A; Siddiqui, A; et al.
Abstract : Background: Moyamoya is a chronic occlusive cerebrovascular disease of unknown etiology causing neovascularization of the lenticulostriate collaterals at the base of the brain. Although revascularization surgery is the most effective treatment for moyamoya, there is still no consensus on the best surgical treatment modality as different studies provide different outcomes. Objective: In this large case series, we compare the outcomes of direct and indirect revascularization and compare our results to the literature in order to reflect on the best revascularization modality for moyamoya. Methods: We conducted a multicenter retrospective study in accordance with the Strengthening the Reporting of Observational studies in Epidemiology (STROBE) guidelines of moyamoya affected hemispheres treated with direct and indirect revascularization surgeries across 13 academic institutions predominantly in North America. Results: The rates of symptomatic strokes were comparable between the two cohorts (9.4% in both cohorts, OR=1.00 [0.537–1.860], p=1.000). The rate of peri-operative major (2.1% for DR vs 1.3% for IR, OR=1.681 [0.397–7.117], p= 0.480), minor (2.6% for DR vs 2.1% for IR, OR=1.205 [0.363–4.005], p= 0.761), and total strokes (4.7% for DR vs 3.4% for IR, OR=1.393 [0.550–3.529], p= 0.484) was comparable between both cohorts. The rate of total follow-up strokes was higher in the IR cohort (7.3% vs 5.6%, p=0.452). Conclusion: Both modalities showed comparable rates of peri-operative strokes, while IR seemed to be associated with a higher rate of strokes during the follow-up period. Thus, when both modalities are indicated, one should take into consideration the superior safety profile of direct revascularization. Disclosures: K. El Naamani: None. C. Chen: None. R. Jabre: None. H. Saad: None. J. Grossberg: None. A. Dmytriw: None. A. Patel: None. M. Khorasanizadeh: None. C. Ogilvy: None. A. Thomas: None. A. Monteiro: None. A. Siddiqui: None. G. Cortez: None. R. Hanel: None. G. Porto: None. A. Spiotta: None. A. Piscopo: None. D. Hasan: None. M. Ghorbani: None. J. Weinberg: None. S. Nimjee: None. K. Bekelis: None. M. Salem: None. J. Burkhardt: None. A. Zetchi: None. C. Matouk: None. R. Abbas: None. G. Sioutas: None. A. Amllay: None. A. Munoz: None. E. Atallah: None. N. Herial: None. S. Tjoumakaris: None. M. Gooch: None. P. Jabbour: 2; C; Medtronic, Microvention, Balt, Cerus Endovascular.